The Moderating Effect of Content Quality on Promotion and Purchase Decisions at Guscio Fashion Brand - Ramdani, Rizki; Dede Kurnia; Ismail Yusup (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Fluctuating sales revenue at the Guscio fashion brand during 2024–2025 indicates that consumer purchase decisions have not been consistently established. A preliminary survey found that although all respondents had seen Guscio's promotions, most had not purchased, considered the content unattractive or unconvincing, and felt that the promotions had not encouraged them to buy. This study describes promotion and purchase decisions, analyzes the effect of promotion on purchase decisions, and examines content quality as a moderator. A quantitative method was used, involving 176 Guscio customers selected by purposive criteria. Data were collected via a Likert scale questionnaire and analyzed using Hayes’ PROCESS Macro Model 1 with bootstrapping at a 95% confidence level. The results show that promotion has a positive and significant effect on purchase decisions, and that content quality significantly moderates this effect by acting as an enhancing moderator, meaning that higher content quality strengthens the influence of promotion on purchase decisions. These findings suggest that Guscio should pair its promotional activities with relevant, informative, and attractive content to improve consumer purchase decisions.